2020
DOI: 10.1029/2019wr025360
|View full text |Cite
|
Sign up to set email alerts
|

Water Management Practices: Use Patterns, Related Factors, and Correlations With Irrigated Acres

Abstract: This study describes the water management practice (WMP) use patterns by producers in Arkansas, USA, identifies the factors related to producers' choices among WMP groups, and examines the correlations between WMP uses and irrigated acreage. Using data from the 2016 Arkansas Irrigation Survey, WMPs are divided into four groups: field management, water flow control, water recovery/storage, and advanced irrigation scheduling practices. We find that about 77% of producers in the study area use two or more groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 33 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…The factors selected are irrigated area in the operation, Groundwater (GW) use in irrigation, crop choice (rice), number of years farming, years of formal education, whether the farmer perceives a GW problem at the farm or state level, average pumping cost in the county of residence, participation in a conservation program, and annual income levels. These factors obtained a sufficient number of valid responses in the sample and were mentioned in two recent comprehensive reviews of the literature [6,22] that identified factors associated with the adoption of agricultural conservation practices or in a recent study of conservation practice adoption in Arkansas [4].…”
Section: Factors Affecting Conservation Practicesmentioning
confidence: 99%
See 4 more Smart Citations
“…The factors selected are irrigated area in the operation, Groundwater (GW) use in irrigation, crop choice (rice), number of years farming, years of formal education, whether the farmer perceives a GW problem at the farm or state level, average pumping cost in the county of residence, participation in a conservation program, and annual income levels. These factors obtained a sufficient number of valid responses in the sample and were mentioned in two recent comprehensive reviews of the literature [6,22] that identified factors associated with the adoption of agricultural conservation practices or in a recent study of conservation practice adoption in Arkansas [4].…”
Section: Factors Affecting Conservation Practicesmentioning
confidence: 99%
“…The hypotheses with respect to this association are drawn from the existing literature. Specifically, we draw from a study using similar data in an adjacent area by Nian et al [4], a comprehensive review of 102 papers in the agricultural conservation practice adoption literature by Prokopy et al [22], and a 129 page Government Accountability Office report to Congress on Irrigated Agriculture by Pearsons and Morris [6]. In terms of the signs of the regression coefficients, the hypotheses are as follows:…”
Section: Factors Affecting Conservation Practicesmentioning
confidence: 99%
See 3 more Smart Citations